Desain Interior Gedung Kesenian Jakarta - Sri Rachmayanti (Bina Nusantara University, 2011)
The purpose of this study was to examine the interior design of Gedung Kesenian Jakarta in detail. Another thing is to obtain complete data and analyze the interior design development of GKJ. This study will described in terms of design style and different designs since the early period of this building, the arrival of the Dutch until the present era. Besides aesthetic of interior design, it will review technical factors in the building that related to its interior design, such as acoustic, air conditioning, lighting system, sound system. This research is based on data literartures and interviews with the GKJ. In conclusion, it will discuss the existence of GKJ in relation to local identity, culture and heritage.